Intensive Technology of Mosh Cultivation in Khorazm Region - BabadjanovaSh.К; NajimovaS.R (Zien Journals, 2023)
This article describes the technology of cultivation, methods and also increasing the yield of mung bean grain as a repeat crop after winter wheat in conditions of irrigated meadow alluvial soils.
Keywords: nodule baсteria; biomass; efficiency; fertilizer